Evolving paradigms in clinical pharmacology and therapeutics for the treatment of Duchenne muscular dystrophy. Issue 2 (20th June 2016) - Huard, J; Mu, X; Lu, A
Abstract : Progressive muscle weakness and degeneration due to the lack of dystrophin eventually leads to the loss of independent ambulation by the middle of the patient's second decade, and a fatal outcome due to cardiac or respiratory failure by the third decade. More specifically, loss of sarcolemmal dystrophin and the dystrophin‐associated glycoprotein (DAG) complex promotes muscle fiber damage during muscle contraction. This process results in an efflux of creatine kinase (CK), an influx of calcium ions, and the recruitment of T cells, macrophages, and mast cells to the damaged muscle, causing progressive myofiber necrosis. For the last 20 years, the major goal in the development of therapeutic approaches to alleviate muscle weakness in DMD has been centered on the restoration of dystrophin or proteins that are analogous to dystrophin, such as utrophin, through a variety of modalities including cell therapy, gene therapy, gene correction, and the highly promising techniques utilizing CRISPR/Cas9 technology. Despite the development of new therapeutic options, there still exist numerous challenges that we must face with regard to these new strategies and, consequently, we still do not have any feasible options available to ultimately slow the progression of this devastating disease. The purpose of this article is to highlight the current knowledge and advancements in the evolving paradigms in clinical pharmacology and therapeutics for this devastating musculoskeletal disease.